2023
DOI: 10.1108/lodj-01-2023-0044
|View full text |Cite
|
Sign up to set email alerts
|

Linking authentic leadership and employee turnover intention: the influences of sense of calling and job satisfaction

Abstract: PurposeThis research aims at examining how authentic leadership impacts social workers' withdrawal behaviors through two intermediate mechanisms: sense of calling and job satisfaction.Design/methodology/approachA cross-sectional survey was distributed among social workers from 26 social work organizations in the cities of Guangzhou, Shanghai, and Shenzhen in China (N = 667). SPSS was used to conduct preliminary analyses and structural equation modeling (SEM) was used to test the hypotheses developed.FindingsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…The previous research (Hussien et al, 2022;Khan et al, 2021) proposes that ES and TI are also associated with effective HRP. Liu and Wong (2023) found that social workers' SOC actually acted as a suppressor variable in the link between turnover intention and leadership as one of the HR practices. Similarly, Huang et al (2022) reveal that calling had a positive moderating effect on the path of job resources and job satisfaction.…”
Section: Hypotheses Development Relationship Between Hrp Es and Timentioning
confidence: 99%
See 2 more Smart Citations
“…The previous research (Hussien et al, 2022;Khan et al, 2021) proposes that ES and TI are also associated with effective HRP. Liu and Wong (2023) found that social workers' SOC actually acted as a suppressor variable in the link between turnover intention and leadership as one of the HR practices. Similarly, Huang et al (2022) reveal that calling had a positive moderating effect on the path of job resources and job satisfaction.…”
Section: Hypotheses Development Relationship Between Hrp Es and Timentioning
confidence: 99%
“…Xie et al (2017) emphasize that employees motivated by internal awards experience higher job satisfaction. On the other hand, Liu and Wong (2023) express that a greater endorsement of a calling among employees is associated with favorable work outcomes, including job satisfaction. In addition, WCT argues that employees' job satisfaction depends on having a SOC (Duffy et al, 2018).…”
Section: Hypotheses Development Relationship Between Hrp Es and Timentioning
confidence: 99%
See 1 more Smart Citation